ChemInform Abstract: Chemoselective and Direct Functionalization of Methyl Benzyl Ethers and Unsymmetrical Dibenzyl Ethers by Using Iron Trichloride. Issue 35 (2nd September 2014) - Sawama, Yoshinari; Goto, Ryota; Nagata, Saori; Shishido, Yuko; Monguchi, Yasunari; Sajiki, Hironao
Abstract For the first time azidation, alkynylation, and cyanation with methoxy and benzyloxy functionalities as leaving groups is presented using FeCl3 as inexpensive catalyst.